1992
DOI: 10.1111/j.1755-3768.1992.tb02096.x
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation syndrome and extracapsular cataract extraction with implantation of posterior chamber lens

Abstract: Extracapsular cataract extraction followed by implantation of a one-piece posterior chamber polymethylmethacrylate intraocular lens (IOL) into the capsular bag was performed in 25 eyes with exfoliation syndrome and 20 control eyes. The patients were investigated preoperatively and then 1 day, 1 week, 3, 6 and 12 months after surgery. Preoperatively, maximal pupil dilatation was significantly smaller in eyes with exfoliation syndrome compared to controls. During surgery the incidence of complications such as ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Earlier studies report a 5-fold to 10-fold increased risk for surgical complications when cataract surgery is performed in eyes with PXF versus non-PXF eyes. 2,34,35,[37][38][39][40][41][42][101][102][103][104] However, more recent studies, with experienced surgeons using technique modifications and adjunctive devices, report this difference to be less. 36,44,105 Some surgeons advocate proceeding to cataract surgery earlier in PXF eyes to avoid the increased risk for complications in the more advanced, dense cataracts with pupil and zonule issues.…”
Section: Pseudoexfoliation and Cataract Surgerymentioning
confidence: 99%
“…Earlier studies report a 5-fold to 10-fold increased risk for surgical complications when cataract surgery is performed in eyes with PXF versus non-PXF eyes. 2,34,35,[37][38][39][40][41][42][101][102][103][104] However, more recent studies, with experienced surgeons using technique modifications and adjunctive devices, report this difference to be less. 36,44,105 Some surgeons advocate proceeding to cataract surgery earlier in PXF eyes to avoid the increased risk for complications in the more advanced, dense cataracts with pupil and zonule issues.…”
Section: Pseudoexfoliation and Cataract Surgerymentioning
confidence: 99%
“…Interestingly, in a recent open study, implantation of HSM IOLs produced no unexpected reactions or severe complications ). However, in the latter study evidence of exfoliation material was not reported and the incidence of postoperative inflammatory cellular reaction with synechia formation is higher in eyes with exfoliation syndrome compared to controls (Zetterstrom et al 1991).…”
Section: Discussionmentioning
confidence: 96%
“…Ocular manifestations of pseudoexfoliation have been well defined, such as PEXG, cataract formation, zonular instability, etc. Pseudoexfoliation fibers also have been identified in many extra-ocular tissues, such as the heart, lung, gall bladder, kidney, and cerebral meninges, so the search for systemic implications of this syndrome has attracted a great deal of attention [11].PEXS is the most common cause of secondary glaucoma worldwide, and the most frequent cause of unilateral glaucoma. PEXG responds poorly to medical therapy compared with other types of glaucoma and can lead to rapid progression of optic nerve damage [12].…”
Section: Discussionmentioning
confidence: 99%
“…Thus the assessment of anterior segment parameters, such as anterior chamber depth (ACD), anterior chamber volume (ACV) and anterior chamber angle (ACA) is an important part of ophthalmic examination in patients with pseudoexfoliation and POAG [10]. A small anterior chamber depth may indicate zonular instability in eyes with PEXS and should alert the cataract surgeon to the possibility of intraoperative complications [11]. In recent years, different devices for anterior segment evaluation have been used, such as slit lamp optic coherence tomography, ultrasonic biomicroscopy, orbscan scanning slit topography, scanning peripheral ACD analyzer and Pentacam Scheimpflug imaging.…”
Section: Introductionmentioning
confidence: 99%